Determining Customer Preferences in Choosing a Marketplace Using the Conjoint Analysis Method - Agustina, Sri; Sirait, Haposan; Salih, Yasir (Communication In Research And Publications, 2023)
The number of online shopping transactions in Indonesia has grown over the last ten years by 17% and the total number of e-commerce businesses has reached 26.2 million units. This creates competition that requires companies to maintain their existence by understanding consumer psychology. This study aims to determine the combination of attribute levels that are most preferred by consumers in choosing a marketplace as a place to shop by using conjoint analysis. The data used is the result of a survey of Riau University students in the form of a questionnaire. The results of the conjoint analysis in this study show that the level of each attribute that respondents prefer is the display of full color applications and images, free shipping promotions on a certain amount of purchase, the method of paying Cash On Delivery (COD), using J&T/JNE/Sicepat/Tiki/Pos delivery services, and product reviews are available in the form of photos and videos.